Determinants of the Use of Accounting Information in MSMEs with Environmental Uncertainty as Moderation - Wulansari Mustofa, Alifiah; Trisnaningsih, Sri (Journal of World Science, 2023)
The Indonesian government has assisted micro small and medium enterprises (MSMEs) in addressing their main problems through the KUR program. In order to complement the KUR program from the government, MSMEs requires the use of accounting information as a basic capital in decision making. This study aims to determine and analyze the influence of independent variables on dependent variables with moderation by a third variable. This research uses a quantitative method. Primary data in this study were obtained from a sample of 93 MSMEs Food entrepreneurs in Surabaya registered in E-PEKEN. This study used Moderated Regression Analysis (MRA) with IBM SPSS Statistics 25 software as an analysis tool. The results of the study indicate that (1) accounting knowledge influences the use of accounting information; (2) accounting training influences the use of accounting information; (3) business scale influences the use of accounting information; (4) environmental uncertainty weakens the influence of accounting knowledge on the use of accounting information; (5) environmental uncertainty strengthens the influence of accounting training on the use of accounting information; (6) environmental uncertainty strengthens the influence of business scale on the use of accounting information. This study implies that accounting knowledge, accounting training, and business scale should be a priority for food MSMEs entrepreneurs in Surabaya registered in E-PEKEN. In facing environmental uncertainty, food MSMEs entrepreneurs in Surabaya must optimize the available resources. Food MSME entrepreneurs in Surabaya should consider business scale as an important determinant factor in the use of accounting information.